2023
DOI: 10.1007/s00330-023-10180-7
|View full text |Cite
|
Sign up to set email alerts
|

Membranous urethral length measurement on preoperative MRI to predict incontinence after radical prostatectomy: a literature review towards a proposal for measurement standardization

Thierry N. Boellaard,
Margriet C. van Dijk-de Haan,
Stijn W. T. P. J. Heijmink
et al.

Abstract: Objectives To investigate the membranous urethral length (MUL) measurement and its interobserver agreement, and propose literature-based recommendations to standardize MUL measurement for increasing interobserver agreement. MUL measurements based on prostate MRI scans, for urinary incontinence risk assessment before radical prostatectomy (RP), may influence treatment decision-making in men with localised prostate cancer. Before implementation in clinical practise, MRI-based MUL measurements need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The AUC of the model stands at 78.2%, indicating a moderate level of accuracy. Several studies and meta-analyses [ 10 , 31 , 32 ] have also demonstrated that MUL is the most studied and reliable urethral parameter to integrate a prediction tool [ 21 ]. Our investigation similarly demonstrated the significant contribution of a longer MUL to UC recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AUC of the model stands at 78.2%, indicating a moderate level of accuracy. Several studies and meta-analyses [ 10 , 31 , 32 ] have also demonstrated that MUL is the most studied and reliable urethral parameter to integrate a prediction tool [ 21 ]. Our investigation similarly demonstrated the significant contribution of a longer MUL to UC recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that MRI measurement might have moderate interrater agreement which is a bias for the generalization of our results based on a single rater [ 39 , 44 ], an issue which may soon be solved by automated MRI measurements [ 45 ]. We attempted to mitigate this limitation by following a standardized protocol for midsagittal MUL measurements [ 20 , 21 ] and as such we believe it does not affect our conclusions [ 39 ]. Other limitations include a pre-operative lack of assessment for the presence of lower urinary tract symptoms which could affect UC recovery, a single institution perspective and a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 45 ]. Boellaard et al [ 46 ] proposed new standardized recommendations to correctly measure MUL on MRI. More specifically, they suggest evaluating it in sagittal T2WI since coronal images typically lack parallel angulation to the MU and to identify the hyperintense urethral lumen and dorsal hypointense membranous structure on one of the midsagittal images.…”
Section: What To Look For On Mr Images Before Surgery To Avoid Compli...mentioning
confidence: 99%